Peranan Motivasi Pimpinan Dalam Meningkatkan Kinerja Penyuluh Keluarga Berencana Di Kota Bandarlampung - . Asmaria (PUBLICA, 2011)
The implications of family planning goals are not only merely to reduce the number of births but also to improve the quality of the population, the quality of human resources and the health and social welfare that have been done through the setting of birth, maturation age of marriage and increasing the family endurance and welfare.Achieving those family planning goals are closely linked to the role of Family Planning Counselors (FPC). Family Planning Counselors help to provide the information and motivation, distribute contraceptives and perform data collection on families. Family Planning Counselors are also have been utilized by other sectors, particularly in Deviating poverty and network support community participation in family planning programs.Similarly, the heavy duty and responsibility of Family Planning Counselors would require the motivation to improve their performance, so the writer is interested to study this problem with the title of how is the role of motivation in improving the motivation of family planning counselors in Bandar Lampung city.In answering this problem the author uses the descriptive qualitative research method. Data were collected by library and field methods, such as observation field, depth interview, and documentation. The sources of information in this research are family planning counselors, other related and authorized party and PUS as the party that knows well about the family planning counselors. The interview results were analyzed to be drawn a conclusion. The results of the research showed that the performance of family planning counselors in Bandar Lampung city is determined by the motivation given in the form of additional incentives, clarity of career (promotion) and the provision of complete working equipment.